2006
DOI: 10.1007/bf02743161
|View full text |Cite
|
Sign up to set email alerts
|

Use of a modified informed consent process among vulnerable patients: a descriptive study

Abstract: JGIM ERRATAWindish DM, Diener-West M. A clinician-educator's roadmap to choosing and interpreting statistical tests. J Gen Intern Med. 2006;21:656-660. The following information was inadvertently omitted from this manuscript: Supplementary MaterialThe following supplementary material is available for this article online at www.blackwell-synergy.com Appendix I. Diagrammatic approach to choosing summary measures, statistical tests, and methods.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
105
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(108 citation statements)
references
References 0 publications
3
105
0
Order By: Relevance
“…We used an interactive consent process, as previously described. (21) This study was approved by the UCSF-SFGH institutional review boards.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We used an interactive consent process, as previously described. (21) This study was approved by the UCSF-SFGH institutional review boards.…”
Section: Methodsmentioning
confidence: 99%
“…We hypothesized that participants would rate the redesigned advance directive easier to use and understand, more useful for personal treatment decisions, and more valuable for care planning. Because the hospital in which the redesigned advance directive was to be implemented has a large proportion of Spanish-speaking patients and patients with limited literacy, (20,21) and because engagement in advance care planning has been shown to be lower in minorities and subjects with lower education, (9,(22)(23)(24) we also explored whether the effects of the redesigned form were greater among participants with limited literacy and among Spanish-speakers.…”
Section: Introductionmentioning
confidence: 99%
“…We excluded patients who could not confirm understanding of the consent process. 22 For this study, we excluded those who died before discharge, were completely dependent in all ADLs at baseline, did not have information on at least four ADLs at each interview, or did not have 30-day follow-up. Participants who completed the baseline interview received a $10 pharmacy or grocery store gift certificate.…”
Section: Design Overviewmentioning
confidence: 99%
“…While most authors have found benefits from designing consent forms that are shorter and easier to read (Coyne et al, 2003;Flory and Emanuel, 2004;Kang et al, 2009;Paris et al, 2010) simply decreasing the reading level will not ensure that all potential participants give consent and authorization that have been substantively informed. For example, easy-to-read consent forms might not be enough for potential research participants who lack familiarity with providing informed consent or the activities of participating in research (Sudore et al, 2006).…”
mentioning
confidence: 99%